The aesthetic as a mediator of the moral and the politics in the history of reason: An approach to aesthetic theory of Friedrich Schiller - Casadesús, Ricard (Pensamiento. Revista de Investigación e Información Filosófica, 2013)
Historic and rationalistic methods are for Schiller the only valid to truly understand the humanbeing. The great merit of Schiller was to have broken the subjectivity and the abstract nature of kantian thought and to have dared, under them, trying to catch by the thought the unity and the conciliation as constituent elements of the truth, and trying to artistically accomplish this conception. Schiller well-combines these three faculties of the spirit and offers an image of the whole man. These faculties, in Schiller, are converted in dynamic dialectic entities, those finally are combined in a higher harmony. So with this maybe built a state. Schiller comes to the conclusion that to solve the political question is necessary to passimmediately by the universe of the art because the way of liberty passes through the beauty.